Induction of salt tolerance in Brassica rapa by nitric oxide treatment - Bano, Atiyyah; Noreen, Zahra; Tabassum, Fariha; Zafar, Fizza; Rashid, Madiha; Aslam, Muhammad; Shah, Anis Ali; Shah, Adnan Noor; Jaremko, Mariusz; Alasmael, Noura; Abdelsalam, Nader R.; Hasan, Mohamed E. (Frontiers in Plant Science, 2022)
Salinity is among the major plant abiotic stresses expanding overtime. The most important biological role of nitric oxide in plants is related to its development and growth under abiotic conditions. Present experiment was conducted to study the effect of salt stress (100 mM) and nitric oxide (80 μM) on two different ecotypes; PTWG-HL and PTWG-PK of Brassica rapa L. Different growth attributes, biochemical and physiological parameters, antioxidant activities and mineral contents were examined. Results indicated the increased hydrogen peroxide (H2O2), relative membrane permeability, malondialdehyde (MDA), Na+ content and decreased plant biomass in ecotypes PTWG-PK and PTWG-HL under salt stress. In contrast, the nitric oxide treatment showed increased plant biomass, chlorophyll, total soluble proteins and decreased H2O2, relative membrane permeability, MDA, total phenolic contents, CAT, POD, APX and Na+. Combined effect of salt stress and nitric oxide increased chlorophyll a, total phenolic contents and total soluble proteins while decreased H2O2, relative membrane permeability, MDA and Na+. Response of carotenoids, anthocyanins, K+, Ca+2, and Cl- ions was variable in all the ecotypes under all treatments. Overall growth response of PTWG-PK was maximum with the application of nitric oxide treatment.